Impact of Chagas Disease in Bolivian Immigrants Living in Europe and the Risk of Stigmatization - Rafael M. Ortí-Lucas; María C. Parada-Barba; José E. de la Rubia-Ortí; Alejandra Carrillo-Ruiz; María Beso-Delgado; An L. D. Boone (Journal of Parasitology Research)
Background. The prevalence of Chagas disease in endemic countries varies with the kind of vector involved and the socioeconomic conditions of the population of origin. Due to recent immigration it is an emerging public health problem in Europe, especially in those countries which receive immigrant populations with a high prevalence of carriers. The study reviews the impact of the disease on Bolivian immigrants living in Europe, the preventive measures and regulations applied in European countries, and their repercussion on possible stigmatization of certain population groups. Methods. The Bolivian immigrant population resident in 2012 was estimated and the affected population in different European countries was calculated with data on carrier prevalence that were recently published. The preventive measures and regulations available in Europe were also reviewed. MEDLINE-PubMed, GoPubMed, and Embase were consulted for the literature review. Results. The Bolivian immigrant population has the highest prevalence of Chagas carriers (6.7%–25%) compared to the overall Latin American population (1.3%–2.4%). Only in Spain, France, Belgium, UK, Portugal, Italy, Switzerland, The Netherlands, and Germany, preventive measures are applied to this population. The established regulations are insufficient and completely different criteria are applied in the different countries and this could reflect a certain degree of stigmatization.